2020
DOI: 10.1055/s-0040-1701442
|View full text |Cite
|
Sign up to set email alerts
|

Older Patients May Have More Frequent Seizures among Children Diagnosed as Benign Convulsions with Mild Gastroenteritis

Abstract: Purpose Benign convulsions with mild gastroenteritis (CwG) is a condition that does not usually require treatment. However, when the patient experiences multiple seizures or prolonged seizures, anticonvulsant treatment may be required. We investigated this study to identify the factors that may influence on the number or duration of seizures at CwG. Methods We retrospectively analyzed the medical records of CwG patients who were admitted to the Department of Pediatrics at Sanggye Paik Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…However, a single-center study reported a positive correlation between the age and frequency of convulsions in CWG, with older children experiencing more seizures. [23] The different outcomes may be related to population differences and further multicenter studies are needed. Rotavirus was previously considered to be the main pathogen of CWG, but with the prevalence of the rotavirus vaccine, the infection rate in CWG has decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, a single-center study reported a positive correlation between the age and frequency of convulsions in CWG, with older children experiencing more seizures. [23] The different outcomes may be related to population differences and further multicenter studies are needed. Rotavirus was previously considered to be the main pathogen of CWG, but with the prevalence of the rotavirus vaccine, the infection rate in CWG has decreased.…”
Section: Discussionmentioning
confidence: 99%
“…CwG commonly occurs in children aged <6 years and peaks at age 12-24 months. [10][11][12][13][14][15]17,[25][26][27][28][29][30][31][32][33][34][35][36] The ratio of male to female patients with CwG was reportedly 1:0.7-2.6. 11,15,17,[27][28][29][30][31][32][33][34][35][36] In addition, it mainly occurs between October and May.…”
Section: Epidemiologymentioning
confidence: 99%